A novel bispecific diabody targeting both vascular endothelial growth factor receptor 2 and epidermal growth factor receptor for enhanced antitumor activity. (13th February 2016) - Xu, Menghuai; Jin, Haizhen; Chen, Zhiguo; Xie, Wei; Wang, Youfu; Wang, Yang; Wang, Min; Zhang, Juan; Acheampong, Desmond Omane
Abstract : Epidermal growth factor receptor (EGFR) and vascular endothelial growth factor receptor 2 (VEGFR2) are receptor tyrosine kinases known to play critical roles in the development and progression of tumors. Based on the cross‐talk between EGFR and VEGFR2 signal pathways, we designed and produced a bispecific diabody (bDAb) targeting both EGFR and VEGFR2 simultaneously. The bispecific molecule (EK‐02) demonstrated that it could bind to HUVEC (VEGFR2 high‐expressing) and A431 (EGFR overexpressing) cells. Additionally, similar to the parental antibodies, it was able to inhibit proliferation and migration, and induced apoptosis in these cells (HUVECs and A431), demonstrating that it had retained the functional properties of its parental antibodies. Furthermore, the efficacy of EK‐02 was evaluated using the human colon adenocarcinoma cell line HT29 (VEGFR2 and EGFR coexpressing). In vitro assay showed that EK‐02 could bind to HT29 cells, restrain cell growth and migration, and induce apoptosis with enhanced efficacy compared to both parental antibodies. Further, it inhibited the neovascularization and tumor formation on an HT29 cell bearing chicken chorioallantoic membrane (CAM) tumor model in vivo. In conclusion, these data suggest that the novel bDAb (EK‐02) has antiangiogenesis and antitumor capacity both in vitro and in vivo, and can possibly be used as cotargeted therapy for the treatment of EGFR and VEGFR2 overexpressing tumors. © 2016 American Institute of Chemical Engineers Biotechnol. Prog., 32:294–302, 2016